Utilization of Local Materials in Nuwo Sesat: A Strategy for the Sustainability of Traditional Lampung Architecture - Tirta Fajar Agung Sadewo; Panji Kurniawan (ARCHIHUMANUM, 2026)
This study examines the utilization of local building materials in Nuwo Sesat, the traditional house of Lampung, within the context of sustainability and resilience to climatic conditions and natural hazards. Employing a qualitative approach combined with architectural ethnography, data were collected through field observations and in-depth interviews. The findings indicate that locally sourced materials, such as merbau and ulin timber, demonstrate strong performance against extreme weather conditions and exhibit adaptability to the geographical context of Lampung. Furthermore, the study formulates a set of principles for the development of sustainable architecture grounded in local wisdom, emphasizing the integration of traditional knowledge with contemporary environmental considerations.